Spinal Surgery for Parkinson Disease With Camptocormia: Propensity Score–Matched Cohort Study With Degenerative Sagittal Imbalance (DSI). Issue 10 (December 2020) - Park, Hyung-Youl; Ha, Kee-Yong; Kim, Young-Hoon; Oh, In-Soo; Chang, Dong-Gune; Kim, Sang-Il; Jeon, Woong-Ki; Kim, Geon-U.
Abstract : Study design: A propensity score–matched cohort study. Objective: The objective of this study was to compare the radiologic and clinical outcomes of camptocormia in Parkinson disease (PD) with degenerative sagittal imbalance (DSI) patients. Summary of Background Data: Camptocormia in PD and DSI could be characterized by a dynamic deformity. However, no study has directly evaluated the outcomes of patients with camptocormia and DSI. Methods: Thirteen consecutive PD patients undergoing surgical correction for camptocormia were matched in a 1-to-2 format with 26 patients in the DSI group by propensity score–matching. Radiologic outcomes, including paravertebral muscle changes, and clinical outcomes were compared between the 2 groups. The rate of proximal junctional problems and reoperations were assessed. Results: PD patients with camptocormia had significantly greater preoperative coronal and sagittal malalignments (29.9 vs. 16.9 mm, P =0.019; 142.8 vs. 64.4 mm, P =0.0001, respectively) and weakness of paravertebral muscles compared with the DSI patients. Regarding the clinical outcomes, reoperations were significantly higher in the camptocormia group, compared with the DSI group (53.8% vs. 7.7%, P =0.001). Moreover, proximal junctional failure was developed in 8 patients in the camptocormia group, while 1 patient in the DSI group (61.5% vs. 3.8%, P =0.0001). In subgroup analysis, independent risk factors for the proximal junctional failure were the total fusion levels (hazard ratio=0.26, P =0.018) and the degree of fatty changes of the paravertebral muscles (hazard ratio=1.15, P =0.048). Conclusions: PD patients undergoing spinal surgery for camptocormia had global malalignment and higher rates of complications compared with DSI patients. Patients should be appropriately counseled regarding the increased risk of operative complications and closely followed for incipient failure.